Efficient syntheses of KLS-13019 using palladium mediated cross couplings. (6th March 2023) - Kinney, William A.; McDonnell, Mark E.; Freeman, Stanley; Simons, Nick; Han, Chao; Yang, Lanyi
Graphical abstract: Abstract: KLS-13019 is a structural analogue of cannabidiol, that shows improved bioavailability and potency in both preventing and reversing paclitaxel-induced neurotoxicity in vitro and in vivo. KLS-13019 was selected as a development candidate and attention was turned to development of a scalable synthesis. The original synthesis of KLS-13019 was not efficient, regioselective, or high yielding. Two new syntheses are reported that make use of the palladium catalyzed cross couplings to a chemically advanced intermediate 5, dramatically shortening (3–4 steps) and improving the overall yield. In addition, a convenient one pot Boc-cleavage and acetylation procedure is described to avoid impurities generated from a step-wise process.